2014
DOI: 10.4196/kjpp.2014.18.4.327
|View full text |Cite
|
Sign up to set email alerts
|

Fucoidan Promotes the Reconstruction of Skin Equivalents

Abstract: In this study we investigated the effects of fucoidan on the proliferation of fibroblasts and the reconstruction of a skin equivalent (SE). Fucoidan significantly stimulated the proliferation of CCD-25Sk human fibroblasts and Western blot analysis demonstrated that fucoidan markedly increased the expression of cyclin D1 and decreased the expression of p27. Fucoidan was used to reconstruct SE. Immunohistochemical staining showed that the addition of fucoidan to dermal equivalents increased expression of prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…We first investigated the effects of different concentrations of LMF on cellular metabolic activity at 24 and 48 h. As shown in Figure 1, LMF did not cause toxicity in NIH3T3 cells, and cellular metabolic activity was significantly higher after treatment with 75 µg/mL of LMF. According to previous studies, fucoidan enhances the proliferation of NIH3T3 fibroblasts [29], which may be because fucoidan can significantly increase the expression of cyclin D1 and reduce the expression of p27 [30]. Our findings in proliferation of NIH3T3 fibroblasts were compatible with the two previous studies.…”
Section: Lmf Reduced Cell Death In Irradiated Fibroblast Cellssupporting
confidence: 92%
See 1 more Smart Citation
“…We first investigated the effects of different concentrations of LMF on cellular metabolic activity at 24 and 48 h. As shown in Figure 1, LMF did not cause toxicity in NIH3T3 cells, and cellular metabolic activity was significantly higher after treatment with 75 µg/mL of LMF. According to previous studies, fucoidan enhances the proliferation of NIH3T3 fibroblasts [29], which may be because fucoidan can significantly increase the expression of cyclin D1 and reduce the expression of p27 [30]. Our findings in proliferation of NIH3T3 fibroblasts were compatible with the two previous studies.…”
Section: Lmf Reduced Cell Death In Irradiated Fibroblast Cellssupporting
confidence: 92%
“…Mar. Drugs 2020, 18,136 3 of 15 p27 [30]. Our findings in proliferation of NIH3T3 fibroblasts were compatible with the two previous studies.…”
Section: Lmf Reduced Cell Death In Irradiated Fibroblast Cellssupporting
confidence: 92%
“…Many properties of fucoidan have been shown by research including targeting coagulation [5], anti-tumor, immunomodulatory, antioxidant, and anti-inflammatory effects [12][13][14]. It was also reported that fucoidan could contribute to the reconstruction of skin while boosting type I procollagen production and inhibiting matrix metalloproteinase MMP-1 levels induced by UV-B [15,16]. Additionally, dermal wound healing has been reported by this polysaccharide [17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are no officially approved dermatological applications of fucoidan [ 2 ]. We recently reported that fucoidan promotes the proliferation of human fibroblasts [ 3 ]. Furthermore, fucoidan increases expression of proliferating cell nuclear antigen (PCNA) and p63 in the epidermis of a reconstructed skin equivalent [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that fucoidan promotes the proliferation of human fibroblasts [ 3 ]. Furthermore, fucoidan increases expression of proliferating cell nuclear antigen (PCNA) and p63 in the epidermis of a reconstructed skin equivalent [ 3 ]. Therefore, it is feasible that fucoidan may have an influence on epidermal melanocytes.…”
Section: Introductionmentioning
confidence: 99%